1995
DOI: 10.1128/jb.177.21.6126-6136.1995
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a polyketide synthase gene from Streptomyces fradiae Tü2717, which carries the genes for biosynthesis of the angucycline antibiotic urdamycin A and a gene probably involved in its oxygenation

Abstract: A DNA fragment was cloned as cosmid purd8, which encodes a polyketide synthase involved in the production of the angucycline antibiotic urdamycin from Streptomyces fradiae Tü2717. Deletion of the polyketide synthase genes from the chromosome abolished urdamycin production. In addition, purd8 conferred urdamycin resistance on introduction into Streptomyces lividans TK24. Sequence analysis of 5.7 kb of purd8 revealed six open reading frames transcribed in the same direction. The deduced amino acid sequences of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 58 publications
0
72
0
1
Order By: Relevance
“…The genes for the latter product are not expressed during actinorhodin production (48). We have also found two apparent PKS clusters in the kinamycin producer Streptomyces murayamaensis (20), and the urdamycin producer Streptomyces fradiae Tü 2717 also contains two (8). It is possible that the unexpressed clusters from S. rimosus NRRL 3016 and WP 4669 may code for spore pigments.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The genes for the latter product are not expressed during actinorhodin production (48). We have also found two apparent PKS clusters in the kinamycin producer Streptomyces murayamaensis (20), and the urdamycin producer Streptomyces fradiae Tü 2717 also contains two (8). It is possible that the unexpressed clusters from S. rimosus NRRL 3016 and WP 4669 may code for spore pigments.…”
Section: Discussionmentioning
confidence: 68%
“…However, in only some cases has heterologous production of a complete pathway been obtained (18,30,37,38), while in a number of cases the product of the reported PKS genes is entirely unknown (25). During the course of our studies, cloning of portions of gene clusters for two other angucyclinones has been reported, as evidenced by gene disruption experiments (8,19). Our strategy has been to clone fragments of DNA large enough to maximize the likelihood of obtaining heterologous production of the target metabolites as a means of unequivocally confirming the identity of the genes.…”
Section: Discussionmentioning
confidence: 93%
“…1) is identical to that seen for their homologues involved in the biosynthesis of the angucycline antibiotics jadomycin (jadIABCED) (20,26), urdamycin (urdFABCDL) (12,16), landomycin (lanFABCDL) (50), and kinamycin (the proposed kinIABCED locus; accession number AY228175).…”
Section: Resultsmentioning
confidence: 80%
“…1 Previous sequence alignment studies revealed two other putative oxygenase-encoding genes to be present in both landomycin gene clusters, namely, lanE/lndE and lanM/lndM. [3][4][5]14 The similarity of lanE (and therefore also lndE) with urdE [14][15][16] suggested that this gene is most likely involved in the generation of the p-quinone moiety. Therefore, the putative oxygenases LanM/LndM were the best candidates for being responsible for the 6-oxygenation in landomycin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%